2007
DOI: 10.1271/bbb.70199
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Fluid Extracts of Rosemary Leaves Exhibit Potent Anti-Inflammation and Anti-Tumor Effects

Abstract: Supercritical fluid SF-CO2 treatment of Rosemarinus officinalis L. fresh leaves under optimum conditions (80 degrees C at 5,000 psi) yielded 5.3% of extract supercritical fluid extraction (SFE)-80, in which five major active principles were identified by liquid chromatography/mass spectrometry (LC/MS), viz., rosmarinic acid, carnosol, 12-methoxycarnosic acid, carnosic acid, and methyl carnosate. Total phenolic content was 155.8 mg/ gallic acid equivalent (GAE)/g in SFE-80, which showed 1,1-diphenyl-2-picrylhyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 1 publication
1
68
0
3
Order By: Relevance
“…9,10 Recent studies revealed that rosemary EOs have greater biological effects than its extracts since the EOs have higher contents of major bioactive components, especially polyphenols and phenylpropanoids such as rosmarinic acid, carnosic acids, camphor, camphene, α-pinene, β-pinene, borneol, caryophyllene, limonene, terpineol and myrcene. [8][9][10][11][12] P. alba L., known as white poplar, growing in a wide range of environmental conditions, is belonging to the family Salicaceae and native to central and southern Europe. 13 Although there were some previous investigations on the EO of P. alba , to the best of our knowledge, this is the first report of its in vitro anticancer and antiproliferative activities.…”
Section: -5mentioning
confidence: 99%
“…9,10 Recent studies revealed that rosemary EOs have greater biological effects than its extracts since the EOs have higher contents of major bioactive components, especially polyphenols and phenylpropanoids such as rosmarinic acid, carnosic acids, camphor, camphene, α-pinene, β-pinene, borneol, caryophyllene, limonene, terpineol and myrcene. [8][9][10][11][12] P. alba L., known as white poplar, growing in a wide range of environmental conditions, is belonging to the family Salicaceae and native to central and southern Europe. 13 Although there were some previous investigations on the EO of P. alba , to the best of our knowledge, this is the first report of its in vitro anticancer and antiproliferative activities.…”
Section: -5mentioning
confidence: 99%
“…Rosmarinus officinalis (R. officinalis) has been used in the prevention of flap necrosis (5); it is known to exert antimicrobial (6-10), antioxidant (11)(12)(13)(14)(15)(16)(17)(18), anti-inflammatory (19,20), antifungal (6,9,10), antidiabetic (15), anticarcinogenic (13,19), antiplatelet (21), antimetastatic (13,19), antiproliferative (16) and antimutagenic (22) effects.…”
mentioning
confidence: 99%
“…El ácido rosmarínico es un éster de ácido cafeico y ácido 3,4-dihydroxifenilictico del cual se ha demostrado un amplio número de actividades biológicas interesantes tales como anti-depresivo, hepato-protectora, anti-inflamatoria, anti-angiogénico, antitumoral y agente fotoprotector, entre otras (Li et al 2010, Peng et al 2007). El ácido carnósico y carnosol, poseen propiedades anti-bacterianas, anti-mutagénicas, anti-inflamatorias antiproliferativas, anti-tumorigénicas y neuroprotectoras (Izumi et al 2007, Oluwatuyi et al 2004, Peng et al 2007, Satoh et al 2008. El ácido carnósico y el carnosol se considera que representan más del 90% de las propiedades antioxidantes del extracto de romero, son potentes inhibidores de la peroxidación de lípidos y buenos eliminadores de radicales peroxilo (Aruoma et al 1992).…”
Section: Ensayo De Mutagenicidad (Prueba De Ames)unclassified